PENGARUH TINGKAT PENGHASILAN, PENGETAHUAN PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK KENDARAAN BERMOTOR - Adilin, Jihan Mega; Efraim Ferdinan Giri (LPPM STIE YKPN Yogyakarta, 2024)
This study aimr to determine the effect of income evel, tax knowledge, and taxpayer awareness on taxpayer compliance to pay motor vehicle tax. The object of this study was vehicle taxpayers located in Depok District, Sleman Regency, Yogyakarta as many as 60 respondents. This study obtained the results that taxpayer awareness has a positive and significant influence on motor vehicle taxpayer compliance. While the level of income and tax knowledge have a positive but not significant effect on taxpayer compliance in paying vehicle tax.